Pengembangan Electronic Student Worksheet Bercirikan Higher Order Thinking Skill dan Model Learning Cycle 7E pada Materi Elastisitas - Tiyas Rahmawati; Joko Budi Poernomo; Fachrizal Rian Pratama (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2022)
During the pandemic teaching materials are needed that can be used online by educators and students, therefore the researchers developed an electronic student worksheet characterized by higher order thinking skill and the 7E learning cycle model on elasticity materials to determine the level of validity, practicality, and effectiveness. This research is categorized as research and development (R&D) research. The methods used in the research are questionnaires, interviews, and test questions. Research subjects are students of class XI MNS and XII MNS 1Pegandon high school. Electronic student worksheet which was developed in the form of a link, making it easier for educators and students in the learning process. The validation results show that the product and instruments developed are very valid. The level of practicality shows that the product developed is very practical to use. The level of effectiveness of the developed product is obtained based on student learning outcomes and responses. Product development is at a moderate level for its effectiveness on student learning outcomes. The response from students and educator is very good.